(untitled) (Fiep Bulletin - online, 2014)
Enteroparasitosis, about everything schistosomiasis, are serious public health problems that persist in developing countries like Brazil Given this context, the objective of this research was to study the index of intestinal parasites and schistosomiasis in rural riverside zone from the Sitio Gavião in Mogeiro - PB. Was used a field research, looking through a questionnaire and qualitative and also samples collected from local residents, with the objective to find cases positive for intestinal parasites and schistosomiasis in the locality. The parasitological analysis was realized in 80 individuals using the method of Hoffman. The results showed a prevalence of 100 % (80/80) of infection by intestinal parasites. The parasites with frequently higher were: Entamoeba histolytica (72.50%), Ascaris lumbricoides (56.25%), Entamoeba coli (55%), Giardia sp (31.25%). In Relation with the diversity of parasites, 22,50% of infected people showed up monoparasitism, 40% biparasitism and 37.50% multiparasitism. Data from this research confirmed the precarious condition of health and basic sanitation of the Sitio Gavião in Mogeiro - PB. With regard to schistosomiasis, there was no evidence of the case. this profile opens space for new studies that have as focus other diseases, with the objetive to establish control measures, improving the quality of life of the population.